Ta’lim Dalam Al-Quran (Kajian Tafsir Tematik Dalam Al-Quran) - Lailatul Maskhuroh (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2021)
There are three terms in education, namely ta'lim, tarbiyah and ta'dib. This article discusses the meaning of taklim. This research method is literature review. And the results of the study in this research are: ta'lim from mu'allim (Allah) consists of: angels, teaching materials in the form of sciences. The second object consists of: prophets/apostles, teaching materials in the form of species names, al-Kitab (al-Qur'an, Torah, Zabur and Gospel), al-bayan, al-hikmah, ta'wil dreams, al-ahkam , useful science, armor making, animal language, and other sciences. The third object of humans, the teaching materials are writing, the contents of the Bible, sharia, hunting etiquette, administrative science, and other sciences. mu'allim (prophet/apostle) consists of: first, the prophet and his teaching materials are sciences / useful. Second, humans and their teaching materials are the Bible, wisdom, the sciences taught by Allah. The first object of the human mu'allim) consists of: first, humans, the teaching materials are al-Kitab, as-Sunnah, reading, writing, and good sciences. Second, the animal and its teaching material is hunting. The object of the mu'allim (shaitan) is man and his teaching material is magic.